Teaching Professional Ethics: A Comparative Study between Qur’an-Based Teaching Professional Ethics and Modern Professional Ethics - Eka Mahendra Putra (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2025)
Ethics is a fundamental pillar of the teaching profession, as teachers not only serve as transmitters of knowledge but also as moral exemplars for their students. Contemporary educational realities reveal various challenges, including the decline of integrity, weak mastery of competencies, and violations of professional codes of ethics, all of which undermine the quality of education. On the other hand, modern professional ethics has been formulated through competency standards and professional codes, both nationally and internationally, such as the Indonesian Teachers’ Association (PGRI) Code of Ethics and the UNESCO Teacher Code. However, the spiritual and transcendental dimensions remain relatively overlooked. This article aims to analyze the concept of professional ethics for teachers from the perspective of the Qur’an and to compare it with modern professional ethics. The study employs a qualitative library research method using a thematic (maudhū‘ī) approach, semantic analysis of key Qur’anic terms such as ‘ilm, ḥikmah, amanah, and ṣidq, and a comparative framework. The findings reveal that the Qur’an emphasizes teacher ethics in the domains of knowledge, trustworthiness, honesty, exemplary conduct, and moral commitment, whereas modern ethics highlights competency standards and regulatory frameworks. The comparative analysis identifies both convergences and divergences, suggesting that their integration offers a more comprehensive framework of teacher ethics encompassing spiritual, moral, and professional dimensions.